2021
DOI: 10.30994/jgrph.v6i1.314
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dates (Phoenix dactylifera) on Breast Milk Production in Post Partum Mother Day 3-9

Abstract: Mother's Milk (ASI) is the best food for babies that is produced directly from the mother's breast to her newborn baby, because its composition is appropriate for every baby's growth and development, breast milk also contains protective substances that can prevent babies from various infectious diseases . Dates contain iron, protein, fiber, glucose, vitamins, biotin, niacin, folic acid, and minerals such as calcium, sodium, and potassium which can increase breast milk production . The purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The suspension increased the estrogen and progesterone serum levels though LH and FSH didn't change significantly as compared to the control groups. Otify et al [44] studied the effect of pollen extracts in rats using multivariate data analysis to correlate between UPLC-MS results and bioassays. Their results indicated that flavonoid glycosides in the polar butanol fraction and polyunsaturated fatty acids in the non-polar petroleum ether fraction substantially contributed to their fertility enhancing activities.…”
Section: The Effect Of P Dactylifera On Women Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The suspension increased the estrogen and progesterone serum levels though LH and FSH didn't change significantly as compared to the control groups. Otify et al [44] studied the effect of pollen extracts in rats using multivariate data analysis to correlate between UPLC-MS results and bioassays. Their results indicated that flavonoid glycosides in the polar butanol fraction and polyunsaturated fatty acids in the non-polar petroleum ether fraction substantially contributed to their fertility enhancing activities.…”
Section: The Effect Of P Dactylifera On Women Healthmentioning
confidence: 99%
“…The suspension increased the estrogen and progesterone serum levels though LH and FSH didn't change significantly as compared to the control groups. Otify et al [44] . studied the effect of pollen extracts in rats using multivariate data analysis to correlate between UPLC‐MS results and bioassays.…”
Section: Introductionmentioning
confidence: 99%
“…According to Dewi et al (2021), giving 100 grams of dates to postpartum mothers on days 3-9 for seven consecutive days can increase breast milk production. Based on Nengsih et al (2020), giving 250 ml of soy milk can increase breast milk production.…”
Section: Making Soy Milk and Datesmentioning
confidence: 99%
“…The research conducted by Pohan & Lestari in 2022 indicates that providing soy milk can increase breast milk production in breastfeeding mothers, while the study by Dewi et al in 2021 found that consuming dates can increase breast milk production in postpartum mothers from day 3 to day 9. Therefore, the recent research results align with previous findings regarding the increase in breast milk production through the consumption of dates and soy milk.…”
Section: Differences In Breast Milk Volume In the Control And Experim...mentioning
confidence: 99%